Pengaruh Kualitas Pelayanan terhadap Kepuasan Wisatawan serta Dampaknya terhadap Loyalitas - Hary Hermawan (Universitas Sarjanawiyata Tamansiswa, 2018)
The aim of this research is to know the influence of service quality to satisfaction and tourist loyality in Ciater Spa Resort. The method used in this research is descriptive verificative. Method analisis of this research is analisis path with software PLS. The results showed that the quality of service has no significant effect on loyalty, it means that service quality as exogenous variable requires intervening role (variable of satisfaction). Visitor satisfaction at Ciater Spa Resort has a significant effect on visitor loyalty. In addition, the relationship between the two research variables are positive, the increasing customer satisfaction will increase also loyalty, otherwise the decrease in visitor satisfaction will have an impact on the decrease in visitor loyalty. These findings have matched customer loyalty theory in marketing books. So that verifikatif research has been done successfully to verify the theory of loyalty in general. This article at once confirms a model of service theory as well as its relationship with satisfaction and loyalty, while minimizing the possibility of false loyalty so that this model can be used in the implementation of service management.Keywords: service quality, satisfaction, loyality.